(untitled) (Justicia &Derecho, 2019)
Peace, conflicts and transitional justice as support for reparation. Theme of individual but complex tradition when conceiving collective. Reality warned as a partial result of the investigation, since the peace agreement signed on November 24, 2016 between the Colombian State and the insurgent group “Revolutionary armed forces of Colombia, army of the people” (FARC-EP) where the existence of all a development within the international standards of transitional justice and the commitment of non-repetition of the State to prevent the emergence of new victims in the post-agreement generated by him and by third parties. An unprecedented modality of integral reparation, a unique figure worldwide based on: the fundamental rights of new and future generations and peace as a collective and second generation right.